Design and Construction of a Simple Cell Using Salt-Water. - Mfitumukiza, Gerald (Kabale University, 2024)
The majority of the energy usage is predominantly by fossil fuels. However, it has resulted in many environmental problems, including the ozone layer problem. Renewable energy sources have been promoted as an alternative to such fossil fuel sources. There are many kinds of renewable energy sources among which solar energy has become the most favorite in many countries along with water and wind. The purpose of this study was to design and construct a simple cell using salt water.